Patient's self-evaluation of two education programs for age-related skin changes in the face: a prospective, randomized, controlled study - Williams LM; Alderman JE; Cussell G; Goldston J; Hamilton N; Lim AC; Goodman GJ; Halstead MB; Rogers JD (Dove Medical Press, 2011)
Linda M Williams1, Jane E Alderman2, Garry Cussell3, John Goldston4, Neal Hamilton5, Adrian C Lim6, Greg J Goodman7, Michael B Halstead8, John D Rogers81Artisan Rejuvenation Clinic, Fortitude Valley, Queensland; 2The Clinic for Essential Beauty, Adelaide, South Australia; 3The Facial Rejuvenation Clinic, Sydney, New South Wales; 4MacKay Skin Clinic, MacKay, Queensland; 5Concept Cosmetic Medicine, Drummoyne, New South Wales; 6Republic Cosmetic Skin and Laser Clinic, Sydney, New South Wales; 7Dermatology Institute of Victoria, South Yarra, Victoria; 8Allergan Australia, Gordon, New South Wales, AustraliaBackground: An interactive software program (HOYS) has been developed utilizing a database of digital images depicting various aspects and degrees of aging of exposed skin across seven geographic regions, representing a total of 35 facial and extrafacial subregions. A five-point photonumeric rating scale, which portrays age-related skin changes across five decades for each of these subregions, underpins this patient-based interactive self-assessment program. Based on the resulting outputs from this program, an individualized treatment prioritization list is generated for each region where significant differences between the patient's chronological and esthetic ages exist. This provides guidance for the patient and the treating physician on treatment options.Methods: To evaluate the utility of HOYS in the clinic, relative to education programs currently used in Australian private esthetic clinics, a total of 95 esthetically-orientated patients were enrolled in a prospective, randomized, controlled, multicenter study.Results: Compared with a prospective cohort of patients completing a standard education program commonly utilized in Australian esthetic clinics, patients receiving the HOYS education program reported greater empowerment through improved knowledge of specific age-related skin changes. This was associated with a clearer understanding of treatment options available to them, and a perceived ability to participate in the selection of the treatments potentially administered to improve their appearance. These differences between the two education groups were highly significant.Conclusion: Patients completing the HOYS patient education program have an improved understanding of age-related changes to exposed skin of their face, neck, décolletage, and hands. Due to the patient-specific nature of the program, these patients perceive a greater role in the deciding which esthetic treatments should be subsequently administered to enhance their appearance, through an improved understanding of the rationale for these treatments and indeed how they should be prioritized to achieve the best outcome for them.Keywords: patient education, age-related skin changes, HOYS, photonumeric scale, randomized, controlled